Risk Factors of Obesity in Low Income Head Start Children - Beverly Copeland; Allan A. Johnson (European Scientific Journal, ESJ, 2016)
The purpose of the study was to investigate the contributing risk factors of obesity among low income Head Start children, and to determine if there is a correlation between caregivers’ perceptions of their own weight and health status, and that of their children. A cross-sectional descriptive study design was utilized. A convenience sample of 195 Head Start children and caregiver pairs were recruited from two Head Start Organizations within the District of Columbia (DC). Measured heights and weights of children and their caregivers were used to calculate Body Mass Index (BMI). A questionnaire was used to ascertain data on caregivers’ perceptions of their children’s weight status, doctors’ diagnoses of children’s weight/height status, caregivers’ perceptions of their own health condition, and sociodemographic data. Results of the study showed that caregivers’ perceived their overweight/obese children as being of normal weight/height status. The majority of the caregivers misperceived their own health status in a positive way. Significant relationships were found between caregiver educational level and child BMI, and between doctors’ weight advice and child BMI. It was concluded that the caregivers underestimated the prevalence of overweight/obesity among their children, and overstated their own health status. Child BMI status was directly related to caregivers’ educational attainment.